PROSPECTS OF USING RENEWABLE ENERGY SOURCES IN STORAGE AND COOLING OF AGRICULTURAL PRODUCTS - Ruzikulov, G.Yu.; Uzakova, Yu.G.; Ibragimov , U.Kh.; Amirkulov, Dj. (Muqobil energetika, 2023)
In this article, the relevance of using renewable energy sources in the storage and cooling of agricultural products, the advantages and disadvantages of using renewable energy in the storage and cooling of fruits and vegetables, the analysis of the work done and being done in Uzbekistan in the storage and cooling of fruits and vegetables, and the work carried out by foreign scientists analyzes of research works are presented